Oceans '99. MTS/IEEE. Riding the Crest Into the 21st Century. Conference and Exhibition. Conference Proceedings (IEEE Cat. No.9
DOI: 10.1109/oceans.1999.799690
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plowing forces for a finite-width blade in dense, ocean bottom sand

Abstract: A FINITE-WIDTH BLADE -120 J L..'.." ..I_ :: ' k 8 0~ AbstractBurying cable in dense ocean bottom sands requires huge plowing forces. This is because of the "pore water" effect. When compact sand shears, the grains must roll over one another. In so doing the spaces (pores) between the grains expand. Water pressure in these pores must decrease in order to draw in water to keep the pores filled. The drag of this permeating pore water squeezes the grains together, increasing the frictional force that shears the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The sand cone would result in soil-soil shear along the interface, which would increase the resistance to installation. A similar phenomenon was also shown in the work of Coyne and Lewis (1999), when investigating seabed ploughs. Their tests showed that nearly double the force was required when laterally displacing a flat wall in comparison to a plough blade with an angle of 40 o .…”
Section: R a F T 4 Development Of An Analytical Model To Predict The Base Component Of Installation Force And Torquesupporting
confidence: 82%
“…The sand cone would result in soil-soil shear along the interface, which would increase the resistance to installation. A similar phenomenon was also shown in the work of Coyne and Lewis (1999), when investigating seabed ploughs. Their tests showed that nearly double the force was required when laterally displacing a flat wall in comparison to a plough blade with an angle of 40 o .…”
Section: R a F T 4 Development Of An Analytical Model To Predict The Base Component Of Installation Force And Torquesupporting
confidence: 82%
“…According to the force translation theorem, the three forces can be translated so that they converge at a point, and a total resultant force can be synthesized. Since the surfaces of the plowshare are exceptionally complex and diverse, this paper directly cites the relevant assumptions and the derivation process in study of [17] to simplify the simplified model of plow-soil interaction mechanics into a two-dimensional model, and the plowsoil mechanics model is shown in Fig. 2 [18].…”
Section: Force Analysis Of the Spar Plough 21 Force Analysis Of Ploug...mentioning
confidence: 99%
“…It has been shown in plowing force estimation studies (e.g. [28]) that Eq. 4 underestimates the plowing force as it ignores the shearing of the sidewalls and bottom surface as well as the effects of pore water flow.…”
Section: Equation Of Motion Governing Ice Gougingmentioning
confidence: 99%